O álbum no meio do rio : uma cartografia afetiva - Machado, Guilherme Lessa Bica (2014)
This present dissertation is a triple scripture: ficction, essay and diary. In this triple birth, a central question is investigated: the narrative of affection. To surprise this narrative, are invoked some biographical contamination author's, reflections about the process of creative writing and the possibilities and impossibilities of a relationship of identity and belonging of the central character with his people and his homeland.